2007
DOI: 10.1580/06-weme-or-071r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Bouldering: A Prospective Study

Abstract: Bouldering outdoors has an increased risk of injury to the fingers. Preventative measures appear largely ineffective in reducing the number of injuries in both cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(131 citation statements)
references
References 23 publications
8
117
4
2
Order By: Relevance
“…Incidence proportion refers to the probability of an athlete sustaining at least one injury and is calculated by the number of injured athletes divided by the number of athletes at risk (13). In their systematic review Woollings, McKay and Emery (36) injuries/100 participants/year for outdoor and indoor bouldering respectively (11). Our search of the literature failed to find any additional primary studies.…”
Section: Clinical Incidencementioning
confidence: 92%
See 1 more Smart Citation
“…Incidence proportion refers to the probability of an athlete sustaining at least one injury and is calculated by the number of injured athletes divided by the number of athletes at risk (13). In their systematic review Woollings, McKay and Emery (36) injuries/100 participants/year for outdoor and indoor bouldering respectively (11). Our search of the literature failed to find any additional primary studies.…”
Section: Clinical Incidencementioning
confidence: 92%
“…Studies that have estimated the reported prevalence of injuries associated with rock climbing vary between 10% and 81% irrespective of cause; between 10% and 50% for impact injuries (9,11,17,37); between 28% and 81% for non-impact acute trauma injuries (9,11,18); and between 33% to 44% for chronic overuse injuries (1,9,37,38). Variance is likely to be 6 associated with differences in the nature, operational level of performance, frequency of performance and duration of activity between climbing disciplines.…”
Section: Prevalence and Incidence Of Injuriesmentioning
confidence: 99%
“…Activities such as bouldering are, of course, not without their dangers (Josephsen et al, 2007;Woolings et al, 2015). From a legal perspective, the courts have previously considered whether those who put themselves deliberately at risk should be able to seek compensation.…”
Section: Risk and Lifestyle Sportmentioning
confidence: 99%
“…A typical safety measure is the use of a specialised portable pad in order to reduce the prevalence and extent of injuries from falls, which is placed underneath the area the climber is working in. Occasionally, a spotter is used who stands below the climber with arms at the ready to redirect the climber if they fall onto the mat, a technique that helps to prevent direct blows to the climber's head or back, thus maximising the chances of (though not necessarily guaranteeing) a safe landing (Josephsen et al, 2007). It is an accident that occurred whilst bouldering at an activity centre that is the focal point of Maylin, but before discussing the case itself we turn to some remarks about risk and lifestyle sport more generally.…”
mentioning
confidence: 99%
“…In the past 20 years several studies (pro-and retrospectively) were conducted to evaluate the injury and fatality risk of rock [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] , ice 19,20 and mountain climbing [16][17][18][21][22][23][24][25][26][27][28][29][30] . Injury incidence was reported per 1000 hours of sport-specific performance, expedition days, summit attempts or other.…”
Section: Introductionmentioning
confidence: 99%